From last supper to self‐initiated weight loss: Pretreatment weight change may be more important than previously thought. Issue 4 (22nd February 2016) - Kerrigan, Stephanie G.; Schaumberg, Katherine; Kase, Colleen; Gaspar, Monika; Forman, Evan; Butryn, Meghan L.
Abstract : Objective: Evaluate the association between pretreatment and during‐treatment weight change, as well as differences in self‐regulation between those who gain weight, remain weight stable, and lose weight pretreatment. Methods: Data from the first 6 months of a behavioral weight loss study were used. Participants ( n = 283) were weighed at two assessment points (screening visit and baseline) prior to the start of treatment and at every treatment session. Participants were divided into those who gained weight, remained weight stable, or lost weight between the screening visit and the first treatment session. Results: Pretreatment weight change was not significantly associated with during‐treatment change. Weight change from the screening visit to month 6 was significantly different by category, with losses of 11% and 7% for those who lost and gained weight pretreatment, respectively. Weight change from first treatment session to month 6 was not different by category. Poorer self‐regulation was associated with pretreatment weight gain and better self‐regulation with pretreatment weight loss. Conclusions: Pretreatment weight change may not relate to success during behavioral weight loss treatment. Researchers should carefully consider when the "baseline" assessment takes place to reduce bias introduced by pretreatment weight change. Poorer self‐regulation may place individuals at risk for weight gain prior to treatment.